Pacific Controls the Co‐Occurrence of Extreme Positive Indian Ocean Dipole and the Following Summer Tropical Indian Ocean Basin‐Wide Warming - Shaolei Tang; Jing‐Jia Luo; Zhiyuan Zhang (Geophysical Research Letters)
Abstract The extreme positive Indian Ocean Dipole (pIOD) in 2019 was followed by tropical Indian Ocean (TIO) basin‐wide warming in summer 2020, which contributed to severe flooding in the Yangtze River basin. Here, the potential relationship between extreme pIOD and subsequent summer TIO basin‐wide warming is explored using observations and model outputs, revealing that this sequential co‐occurrence is significantly influenced by Pacific SST conditions. Extreme pIODs that coincide with El Niño tend to be followed by TIO basin‐wide warming, whereas those cooccurring with neutral or La Niña conditions are comparatively less likely to do so. This is because El Niño can trigger anomalous anticyclone over the southeastern TIO, thereby maintaining and reinforcing the extreme pIOD‐related warm SST anomalies over the southwestern TIO, which subsequently induces SST warming over the northern TIO in summer. Our findings highlight the important modulation role of Pacific SST conditions, with significant implications for regional climate predictions.